Testing creditor moral hazard in sovereign bond markets: A unified theoretical approach and empirical evidence - Ayşe Y. Evrensel; Ali M. Kutan (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2004)
This paper critically evaluates the existing empirical literature on creditor moral hazard in sovereign bond markets, proposes a unified theoretical approach to test for IMF-induced creditor moral hazard, and provides empirical evidence, using daily sovereign bond market spreads of Indonesia and Korea. The results suggest that IMF-related news regarding program negotiations and approval may be associated with creditor moral hazard, but their impact on spreads is short-lived, indicating that creditor moral hazard could be best described as a short-run phenomenon.
Keywords: F32; F33; F34; 330